Analisis Novel “Bumi dan Lukanya” Karya Revianaaprl Dengan Pendekatan Pragmatik - Fani, Mulyana Mei; Nazwa, Aula; Harti, Aiga Tania; Wardani, Ayu; Chairunnisa, Chika; Rifki, Muhammad; Lubis, Fitriani (Peneliti.net, 2025)
The novel